Project facilitation as an active response to tensions in international development programmes - Lannon, John; Walsh, John N. (International Journal of Project Management, 2020)
This paper examines the tension within international development programmes between traditional task-oriented approaches to development and the wider view of programmes as sites for adaptability and learning. It characterises it as a set of inter-related tensions between recursive and adaptive tendencies that exist at individual actor, programme and institutional levels. Drawing on a multiple interpretive case study of partnership based programmes between an international non-government organisation and local partners in three countries, it looks at how these tensions play out in practice. Based on the findings, it proposes an active response to the tensions called project facilitation. This is an adaptive and co-created process that incorporates local experience and practice based knowledge to achieve strategic goals, while utilising recognised project management practices to achieve agreed outcomes. By adopting active responses to the tensions that exist within programmes it offers greater potential for effective delivery of long term benefits than the more typical defensive response strategies. Project facilitation is consistent with the social constructionist view of programmes and programme management but broadens our understanding by emphasising the need to actively consider how the tensions inherent in programmes are responded to.
Keywords: Adaptive management; International development; Non-governmental organisations; Partnership; Programme management; Project facilitation; Tensions

Celebrating Adaptive Delivery: A View from the Frontline in Myanmar - Barnes, Katrina; Lonsdale, Jane (Institute of Development Studies, 2023)
The conversation on adaptive management has grown fast amongst development actors. These conversations often focus on designing, commissioning, and managing large-scale development programmes. Exactly how this impacts the frontline, the implementers, and day-to-day project delivery is still being debated. Yet, perspectives drawn directly from practice are often largely missing within these debates. This paper is written by two development practitioners. Through this paper, we reflect on the difference between adaptive management and adaptive delivery, and how this interacts with risk and aid accountability, particularly in contexts of fragility. Drawing on examples of Oxfam in Myanmar work and our personal insights in relation to delivering programming across humanitarian, peace-building, and development, we suggest that in complex, conflict-affected, and highly political environments adaptive delivery already happens far more regularly than is currently recognised, as a necessity to get activities delivered. However, it happens despite the system, not because of it, and is therefore often hidden and carried out ‘under the radar’ rather than celebrated as a success in difficult environments. This paper was written in 2019, before the military seized control of Myanmar in February 2021. Whilst it draws on examples from pre-2021 Myanmar to illustrate real life cases, it is a contribution to a broader global debate on adaptive management in practice, specifically in fragile contexts. This is not specifically aimed at practitioners working in Myanmar at present, who are now working in a protracted crisis. This paper makes tangible recommendations on steps that donors, international non-governmental organisations, local staff, and partners could take to promote a system of encouraging and celebrating adaptability in programme delivery in fragile contexts.
Accepted: 2023-02-02T14:48:03Z

Civil society organizations and managerialism: On the depoliticization of the adaptive management agenda - Gutheil, Lena; Koch, Dirk-Jan (Development Policy Review, 2022)
Motivation In the last decade, a movement formed around making aid delivery more adaptive, relying on principles such as context sensitivity, flexibility, and ownership. The approaches seem promising for civil society organizations (CSOs) to fulfil their mission of fostering social transformation. While several donor agencies have started engaging with such approaches, the authors hardly see their political implications in practice. Purpose The article aims to provide evidence on an adaptive project and demonstrate how the social transformative and political nature of adaptive development management is rendered technical and depoliticized in practice. Methods and approach We use a case study of a development programme based on a social transformative policy framework that is implemented through CSOs in Uganda and Vietnam. Data were collected by means of interviews, participant observation and document analysis. Findings We find that, in practice, the social transformative policy framework is competing with managerial logics. We compare this process with the depoliticization of the Paris Declaration on Aid Effectiveness, finding striking similarities. By using practice theory, we show how managerialism remains the dominant paradigm in the civil society aid sector, fuelling the “anti-politics machine.” Policy implications The article shows that policy frameworks do not always work as intended. Donors should therefore not only change policy frameworks, but also start addressing institutional and operational requirements.
_eprint: https://onlinelibrary.wiley.com/doi/pdf/10.1111/dpr.12630

Navigation by Judgment: Why and when Top Down Management of Foreign Aid Doesn't Work - Honig, Dan (Oxford University Press, 2018)
Foreign aid organizations collectively spend hundreds of billions of dollars annually, with mixed results. Part of the problem in these endeavors lies in their execution. When should foreign aid organizations empower actors on the front lines of delivery to guide aid interventions, and when should distant headquarters lead? In Navigation by Judgment, Dan Honig argues that high-quality implementation of foreign aid programs often requires contextual information that cannot be seen by those in distant headquarters. Tight controls and a focus on reaching pre-set measurable targets often prevent front-line workers from using skill, local knowledge, and creativity to solve problems in ways that maximize the impact of foreign aid. Drawing on a novel database of over 14,000 discrete development projects across nine aid agencies and eight paired case studies of development projects, Honig concludes that aid agencies will often benefit from giving field agents the authority to use their own judgments to guide aid delivery. This "navigation by judgment" is particularly valuable when environments are unpredictable and when accomplishing an aid program's goals is hard to accurately measure. Highlighting a crucial obstacle for effective global aid, Navigation by Judgment shows that the management of aid projects matters for aid effectiveness.
Google-Books-ID: GT5MDwAAQBAJ

When theory meets reality: assumptions, feasibility and implications of a complexity-informed approach - Buffardi, Anne (Methods Lab, 2016)
Over the last half century, repeated calls for adaptive learning in development suggests two things: many practitioners are working in complex situations that may benefit from flexible approaches, and such approaches can be difficult to apply in practice. • Complexity thinking can offer useful recommendations on how to take advantage of distributed capacities, joint interpretation of problems and learning through experimentation in complex development programmes. • However, these recommendations rely on underlying assumptions about relationships, power and flexibility that may not hold true in practice, particularly for programmes operating in a risk averse, results-driven environment. • This paper poses guiding questions to assess the fit and feasibility of integrating complexity informed practices into development programmes.

Managing Upward and Downward Accountability in an International Development Project - A Case Study of a World Bank Telecommunications Infrastructure Project in Benin - Kolker, Eva; Kulldorff, Catharina (Master's Thesis, Stockholm School of Economics, 2013)
Keywords: Downward accountability; Upward accountability

How Big Things Get Done: The Surprising Factors Behind Every Successful Project, from Home Renovations to Space Exploration - Flyvbjerg, Bent; Gardner, Dan (Macmillan, 2023)
World expert Bent Flyvbjerg and bestselling author Dan Gardner reveal the secrets to successfully planning and delivering ambitious projects on any scale.Nothing is more inspiring than a big vision that becomes a triumphant new reality. Think of how Apple’s iPod went from a project with a single employee to an enormously successful product launch in eleven months. But such successes are the exception. Consider how London’s Crossrail project delivered five years late and billions over budget. More modest endeavours, whether launching a small business, organizing a conference, or just finishing a work project on time, also commonly fail. Why?Understanding what distinguishes the triumphs from the failures has been the life’s work of Oxford professor Bent Flyvbjerg. In How Big Things Get Done, he identifies the errors that lead projects to fail, and the research-based principles that will make yours succeed:- Understand your odds. If you don’t know them, you won’t win.- Plan slow, act fast. Getting to the action quick feels right. But it’s wrong.- Think right to left. Start with your goal, then identify the steps to get there.- Find your Lego. Big is best built from small.- Master the unknown unknowns. Most think they can’t, so they fail. Flyvbjerg shows how you can.Full of vivid examples ranging from the building of the Sydney Opera House to the making of the latest Pixar blockbusters, How Big Things Get Done reveals how to get any ambitious project done – on time and on budget.

Simplexity² or: How I Learned to Stop Worrying and Love Complexity in Development - Prieto Martin, Pedr (2018)
This seminar is the fifth in a series that aims to share cutting edge thinking and research being done at IDS and the University of Sussex around how we practically capture and account for complexity across a variety of sustainable development contexts. Join us for a fascinating trip from Athens to Xiaogang where, assisted by Steve Jobs, Sun Tzu and Aristotle, and with the help of a series of memorable diagrams, we attempt to alchemise development’s complexity into… a simple living tree. The seminar aims to integrate into an accessible narrative notions from various disciplines related to complexity science –including psychology, philosophy, organisational development and software engineering– as a way to articulate essential complexity concepts. Insights emerging from our cluster’s research on Adaptive Management and on the use of Frontier Technologies for development are linked with ideas presented by Prof. Chambers, Burns, Scoones and Ang in the previous seminars, to explore what complexity means in practice for development professionals and how we can discern and handle it at best. About the Speaker Pedro Prieto Martín is a software engineer turned trans-disciplinary social scientist. Pedro’s academic background includes degrees in Computer Science, Business Administration, Philosophy, and Sociology from different Spanish universities. After working for years at Hewlett-Packard in Germany as the Technical Lead of a development team, he moved to Latin America, where for years he researched the application of ICT to improve local governance and promote social change. Before joining the Digital and Technology cluster he supported and researched, at the local level, the social mobilisation processes that resulted from the “indignados” movement in Spain and their use of ICT. At IDS, Pedro has investigated the drivers of adaptiveness in accountability interventions, as part of MAVC. He now coordinates the learning component of DFID’s “Frontier Technologies Livestreaming (FTL)” programme, which has been recently awarded UK’s Civil Service Award for Innovation. FTL supports DFID country offices to experiment with the use of emerging technologies to address development challenges.